1991
DOI: 10.7326/0003-4819-114-1-54
|View full text |Cite
|
Sign up to set email alerts
|

The Counseling Practices of Internists

Abstract: The low level of self-reported counseling among these internists suggests that further emphasis on training in these skills is needed. The association between personal and professional practices suggests that medical schools and housestaff training programs should support health promotion activities for future internists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
91
5
5

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(112 citation statements)
references
References 9 publications
11
91
5
5
Order By: Relevance
“…30,31 It was, nevertheless, a high prevalence considering the expected physician's role and also as compared to the rates demonstrated by various other reports. [32][33][34][35] The average number of cigarettes consumed per day was almost equal to that reported by Saeed et al 29 There was no significant association between personal lifestyle of this sample of physicians and their counseling practices, although other studies have confirmed that such a relationship often exists. 32,[36][37][38][39] The finding that only one-tenth of PHC physicians used religious reasons in their anti-smoking activities was surprising and discouraging.…”
Section: Discussionsupporting
confidence: 48%
“…30,31 It was, nevertheless, a high prevalence considering the expected physician's role and also as compared to the rates demonstrated by various other reports. [32][33][34][35] The average number of cigarettes consumed per day was almost equal to that reported by Saeed et al 29 There was no significant association between personal lifestyle of this sample of physicians and their counseling practices, although other studies have confirmed that such a relationship often exists. 32,[36][37][38][39] The finding that only one-tenth of PHC physicians used religious reasons in their anti-smoking activities was surprising and discouraging.…”
Section: Discussionsupporting
confidence: 48%
“…(2) How frequently are these discussions occurring? (3) The patients in the study were slightly more likely than not to be female (55%) and Black (59%); they were generally poor (66% earned less than $10 000 per year; 16%, from $10 000 to $20 000; and 18%, more than $20 000). They ranged in age from 23 to 95 years (mean age = 60.5 years).…”
Section: Introductionmentioning
confidence: 99%
“…3 Unfortunately, many of the descriptions of counseling practices are based on surveys and are limited by their reliance on self-report measures. Observational studies of life-style counseling are relatively rare; however, their results are quite consistent. Neither residents45 nor fully trained physicians6,7 appear to be doing an adequate job.…”
Section: Introductionmentioning
confidence: 99%
“…Personal habits affecting the health of PCPs are sometimes considered barriers to health promotion be havior [4,7,8,[23][24][25], We used the body mass index (BMI) of the PCP (as an indication of personal habits affecting health) in our LISREL path analysis (see Table 2) to test whether it was a predisposing factor or an intermediary factor in the model of Fig. 2.…”
mentioning
confidence: 99%